[Observations on Jensen's Experimental Design for Study of Effects of Accounting Variations in Decision Making]: A Rejoinder - Jensen, Robert E. (Journal of Accounting Research, 1967)
Robert E. Jensen, [Observations on Jensen's Experimental Design for Study of Effects of Accounting Variations in Decision Making]: A Rejoinder, Journal of Accounting Research, Vol. 5, No. 2 (Autumn, 1967), pp. 230-251